2019
DOI: 10.1007/s40195-019-00979-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study on the Semiconductive and Dissolution Behaviour of 316L and Alloy 625 in Hydrochloric Acid Solution

Abstract: The corrosion behaviour of 316L and Alloy 625 was investigated using cyclic polarization, electrochemical impedance spectroscopy, X-ray photoelectron spectroscopy, Auger electron spectroscopy and induced coupled plasma-optical emission spectrometer. The results indicated that Alloy 625 showed better corrosion resistance than 316L and the prolonging immersion time could enhance corrosion resistance of the two alloys. The passive film formed on the surface of 316L exhibited an electronic structure of p-p heteroj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The peaks of Cr 2p3/2 in figure 7(a) consist of three peaks, corresponding to metallic Cr (Cr-met, 574.2 eV), Cr 2 O 3 (576.6 eV) and Cr(OH) 3 (577.4 eV). Previous research has shown that the passive film on austenitic stainless steels in 3.5% solution is composed of Cr-met, Cr 2 O 3 and Cr(OH) 3 [4,38]. Feng et al [39] reported that Cr 2 O 3 has a lower point defect density and higher thermodynamic stability than Cr(OH) 3 , making it a more stable component of the passive film.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks of Cr 2p3/2 in figure 7(a) consist of three peaks, corresponding to metallic Cr (Cr-met, 574.2 eV), Cr 2 O 3 (576.6 eV) and Cr(OH) 3 (577.4 eV). Previous research has shown that the passive film on austenitic stainless steels in 3.5% solution is composed of Cr-met, Cr 2 O 3 and Cr(OH) 3 [4,38]. Feng et al [39] reported that Cr 2 O 3 has a lower point defect density and higher thermodynamic stability than Cr(OH) 3 , making it a more stable component of the passive film.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in good agreement with many results in the corrosion eld, i.e., a passive lm of stainless steel had a duallayer structure characterized by the inner layer enriched with Cr 2 O 3 and the outer layer enriched with Fe 2 O 3 . [42][43][44][45] For the cathode electron gain process, the main reaction is the hydrogen evolution reaction on the Cr-rich region. The total reaction formula is:…”
Section: Resultsmentioning
confidence: 99%
“…, a passive film of stainless steel had a dual-layer structure characterized by the inner layer enriched with Cr 2 O 3 and the outer layer enriched with Fe 2 O 3 . 42–45…”
Section: Resultsmentioning
confidence: 99%
“…where Y 0 is a proportionality constant, j 2 = −1 and n is an empirical exponent between 0 and 1. When n = 1, CPE represents a pure capacitive element; when n = 0, CPE represents a resistor; and when n = 0.5, CPE represents Warburg impedance [38]. Figure 7 shows the equivalent circuit diagram used to fit the AC impedance spectrum.…”
Section: Potentiostatic Polarizationmentioning
confidence: 99%